Efficient Photoelectrochemical Reduction of Nitrite to Ammonium and Nitrogen Containing Gaseous Species Using Ti/TiO2 Nanotube Electrodes - Sayao, Fabiana A. [UNESP]; Nunez, Luciana [UNESP]; Zanoni, Maria V. B. [UNESP] (Soc Brasileira Quimica, 2014)
The present work describes a suitable method for removing nitrite contaminant from water by using a photoelectrocatalytical method. A Ti/TiO2 nanotube electrode was used as a cathode under UV irradiation and applied potential of -0.2 V vs. Ag/AgCl and it led to 100% of nitrite removal after 6 min of photoelectrolysis conducted in NaCl 7 mmol L-1, pH 7 and in absence of dissolved oxygen. Nitrite reduction on Ti/TiO2 photoelectrodes occurs in the cathodic compartment cell via electrons generated when the electrode is under UV irradiation leading to a generation of 7% of remaining ammonium and 93% nitrogen containing gaseous species after 6 min of treatment. The results indicate that the method could be an efficient tool for the treatment of nitrite in water containing nitrite.

O presente trabalho descreve uma nova metodologia para remoção de nitrito de águas contaminadas usando o processo fotoeletrocatalítico. Um eletrodo de nanotubos de Ti/TiO2 foi utilizado como fotocátodo sob irradiação UV e potencial aplicado -0,2 V vs. Ag/AgCl e levou a remoção de 100% do nitrito após 6 min de fotoeletrocatálise em solução de NaCl 7 mmol L-1, pH 7 e ausência de oxigênio dissolvido. A redução de nitrito sobre o eletrodo de Ti/TiO2 ocorre no compartimento catódico da célula pelos elétrons fotogerados quando o eletrodo é irradiado com luz UV, gerando 7% de amônio e 93% de espécies gasosas de nitrogênio após 6 min de tratamento. Os resultados indicam que o método pode ser uma ferramenta eficiente para o tratamento de águas contaminadas com nitrito.
Keywords: nitrite; photoelectrocatalysis; TiO2 nanotubes; photocathode